Exploring a rumen-modelled carboxylate platform for the conversion of agricultural wastes to green chemicals and fuels in South Africa - Njokweni, Sesethu Gift (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.